1993
DOI: 10.1073/pnas.90.24.11543
|View full text |Cite
|
Sign up to set email alerts
|

Cloning of the large subunit of activator 1 (replication factor C) reveals homology with bacterial DNA ligases.

Abstract: We have cloned a gene encoding a DNAbinding protein by Southwestern screening of a murine cDNA library with a double-stranded oligonucleotide containing the sequence from the bidirectional promoter of the al and a2 collagen IV genes. The middle portion of this 1131-amino acid protein has a region homologous to bacterial DNA ligases, and the more carboxyl portion contains several domains homologous to p40, p38, p37, and p36.5 subunits of activator 1 (Al, also called replication factor C), a human replication pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
62
0

Year Published

1995
1995
2003
2003

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(64 citation statements)
references
References 37 publications
2
62
0
Order By: Relevance
“…Among several proteins tested, we found that RFC-140, the large subunit of RFC (4,5,44), interacts with Brd4. Extracts from NIH 3T3 cells were first precipitated with anti-Brd4 antibody, and the precipitated materials were tested for RFC-140 by immunoblot analysis.…”
Section: Brd4 Interacts With Rfc In Vivomentioning
confidence: 99%
“…Among several proteins tested, we found that RFC-140, the large subunit of RFC (4,5,44), interacts with Brd4. Extracts from NIH 3T3 cells were first precipitated with anti-Brd4 antibody, and the precipitated materials were tested for RFC-140 by immunoblot analysis.…”
Section: Brd4 Interacts With Rfc In Vivomentioning
confidence: 99%
“…Functional homologs exist in bacteria, some bacteriophages, and Archea (95). The cDNAs encoding the individual subunits of human and the yeast S. cerevisiae RFC have been cloned, and all five yeast genes are essential for cell viability (96)(97)(98)(99)(100)(101)(102)(103)(104). Sequence comparisons show a high degree of similarity among all five subunits, and based on these similarities and the conserved sequences found among species, short stretches of amino acid sequences called RFC boxes I-VIII have been defined (104).…”
Section: Replication Factor C (Rfc)mentioning
confidence: 99%
“…To support these affirmations, the cloning and expression RF-C, PCNA, RP-A and ATP selectively stimulates DNA syn-of the large subunit of RF-C revealed that this subunit preferenthesis by polymerases δ and ε [26]. The possibility to isolate tially binds to dsDNA compared with ssDNA [18,31,32]. stable polymerases δ and ε holoenzymes, assembled on DNA by Using a modified PCNA form that could be phosphorylated RF-C, PCNA and ATP, suggests a direct interaction of the auxil-in vitro and a dsDNA template with a defined gap of 45 nucleoiary proteins with the polymerases [26].…”
Section: Rf-c As a Clamp Loader And Unloadermentioning
confidence: 99%